Sustainability and impact assessment of IPM in Basmati rice (Oryza sativa) - SINGH, S; TANWAR, R K; SINGH, S P (The Indian Journal of Agricultural Sciences, 2022)
Integrated pest management (IPM) strategy has greatly contributed to a progressive commitment for sustainable agriculture in India. Long term studies conducted on validation and promotion of IPM in basmati rice (Oryza sativa L.) in district Gautam Budh Nagar, Uttar Pradesh, India resulted in a gradual enhancement in the area under IPM from 40 ha in 2010 by participation of 25 farmers to 990 ha in 2019 by participation of 654 farmers from 42 villages. Implementation of IPM technology resulted in a significant (P